Thoracic index in adults with asthma: A study of validity and reliability (2018)
Background: The Thoracic Index (TI) is a useful tool for evaluating costal mobility as a component of respiritory mechanics in adults with asthma. In a review of the literature, however, few studies were found that reported the psychometrics of this test. The goal of this study is to evaluate the reproducibility and validity of the TI in adults with asthma. Methods: A cross-sectional study was conducted to evaluate the diagnostic tests. Measurements were done randomly by two independent evaluators. The variables measured included thoracic mobility (TI and photogrammetric analysis), sociodemographic and anthropometric variables, and other variables related to the disease. TI reliability included the determination of the intra- and inter-evaluator agreement and reproducibility using the Bland and Altman limits of agreement method and the Interclass Correlation Coefficient (ICC). The convergent validity was established using Pearson's correlation coefficient. The level of significance was p < 0.05. Results: Twenty-six adults with stable asthma participated in this study. The limits of the intra- and inter-evaluator agreement were found to be acceptable and good, respectively, with an average of differences close to zero in both cases. The intra-evaluator reproducibility was between poor and acceptable (TI between 0.57 and 0.93), while the inter-evaluator reproducibility was between acceptable and good (TI between 0.62 and 0.86). The convergent validity between the TI and photogrammetric analysis was between moderate and high (r between 0.55 and 0.73). Conclusions: The TI is a reliable and valid measurement that can be used to evaluate costal mobility in adults with asthma. In a clinical setting, it can contribute to a nonbiased measurement, and in a research environment, it is useful for documenting the results of interventions, reducing the probability that the results will be affected by any variability in measurement. © 2018 The Author(s).